Oral and Facial Manifestations of COVID-19 Patients - M. Okoh; D.S. Okoh (Nigerian Dental Association, 2020)
Objective: To review the oral and facial manifestations of COVID-19 which may be useful in the prompt diagnosis of the disease. Materials and Methods: Literatures were searched from renowned electronic databases like PubMed, Medline, Google scholar and Cochrane Library. The following words were used for the search. "Oral and facial manifestations of COVID-19." Results: The SARS-CoV-2 virus is transmitted from human to human via droplet transmission and direct contact with oral, nasal, and eye mucous membranes. Studies suggest that COVID-19 may become airborne through aerosols generated during clinical procedures. The most common symptoms of coronavirus disease are fever, tiredness, dry cough and difficulty breathing. Other atypical symptoms, such as muscle pain, confusion, headache, anosmia, dysgeusia, sore throat, diarrhea, and vomiting have been reported, and seem to be on the rise. Conclusion: It will be interesting to determine in the near future how frequent those manifestations are in individuals presenting symptoms in contrast to infected asymptomatic patient, and their usefulness in defining the outcome of COVID-19.